Manajemen Kewirausahaan Berbasis Pendidikan Islam dalam Pengembangan Usaha Kafe (Studi Lapangan pada Cafe YourSpace Leuwiliang Kabupaten Bogor) - Alwi, Rahmawati; Yulianti, Yulianti; Atiyyah, Siti Khodijah; Triandi, Dahryan Azharul; Mustopa, Septian Cahya; Saepudin, Pupud (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2026)
This study examines Islamic education-based entrepreneurship management in developing Cafe YourSpace, Leuwiliang, Bogor, evolved from Jalan Pintas under Pesantren Business Entity. The objective is to analyze Islamic values application in cafe planning, marketing, and human resource management. Employing qualitative case study approach, population comprises cafe managers and employees with purposive sampling of two main managers. Instruments include in-depth interviews, participant observation, and document analysis, descriptively analyzed through data reduction, presentation, and verification. Findings reveal integration of maslahah, taawun, and talab al-ilm values achieving 30-50% revenue increase, customer loyalty via literacy space, and cafe as entrepreneurship laboratory for students. The conclusion states this model is sustainable yet challenged by weather, space limitations, and competition, recommending adaptive innovations and comparative studies.